If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = 5(x + 6) + -7x Reorder the terms: 26 = 5(6 + x) + -7x 26 = (6 * 5 + x * 5) + -7x 26 = (30 + 5x) + -7x Combine like terms: 5x + -7x = -2x 26 = 30 + -2x Solving 26 = 30 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 26 + 2x = 30 + -2x + 2x Combine like terms: -2x + 2x = 0 26 + 2x = 30 + 0 26 + 2x = 30 Add '-26' to each side of the equation. 26 + -26 + 2x = 30 + -26 Combine like terms: 26 + -26 = 0 0 + 2x = 30 + -26 2x = 30 + -26 Combine like terms: 30 + -26 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 11=3(x-3)-(x-6) | | -2k+3k-5+5k= | | 7x-3x-18=2 | | 9x+1=7x+31 | | 18u+v-5+12v= | | 9x-(3x-3)=45 | | y-1=-1/2(x-8) | | x-9x+90=-10 | | 2/3x-10 | | 2y/y-9+1=6y/y-9 | | 14x-3y=180 | | 2-25/x=7 | | x/4+7x/10=x/14 | | 2=-3-1/6x | | 8x/x+8 | | 8U^8*X^9*Y^8+14X^5*Y^4=0 | | 5x+y+3x+5y=180 | | -9-4*-3*-4= | | -9-4(-3x-4)= | | 5x+y=3x+y | | 15=-2x-12 | | (m-6)/m+1/2m=1/4m | | 47+.4167x=100 | | 47+.4167=100 | | 2/3(3t+6)-1/2(5t-6)=4 | | n+(4n-3)/9-5=(2n+1)/3 | | 25s=-175 | | 2w^2-10w+37= | | (6a-5)/6+(4a-5)/4+(8a+9)/12=4 | | .75x+9.5=0 | | x+(2x-7)/9-2=(2x+3)/3 | | -5a+-a+8a+-5b+-b+-8b= |